Investigation of the solution chemistry and dermal absorption of novel copper (II) chelating agents that can serve as potential anti-inflammatory drugs - Mokalane, Kagiso (Department of Chemistry, 2015)
This study describes the investigation of the solution chemistry of the copper (II) complexes of homopiperazine and an adamentane derivative of homopiperazine (PCU.homo) using glass electrode potentiometry, UV/VIS spectroscopy, speciation modeling, nuclear magnetic resonance spectroscopy, blood plasma modeling, and dermal absorption.